Fundamental biomechanics of sport and exercise - Watkins, James (Routledge, Taylor & Francis Group, 2014)
Fundamental Biomechanics of Sport and Exercise is an engaging and comprehensive introductory textbook that explains biomechanical concepts from first principles, showing clearly how the science relates to real sport and exercise situations. Every chapter includes numerous applied examples from sport and exercise, helping the student to understand how mechanical concepts describe both simple and complex movements, from running and jumping to pole-vaulting or kicking a football. This is an essential textbook for any biomechanics course taken as part of degree programme in sport and exercise science, kinesiology, physical therapy, sports coaching or athletic training.